Freshman University Student Approaches to Learning Strategies: Impact on Academic Performance - Moreno, Jacqueline Elizabet (2020)
This study describes learning strategies used by engineering students attending the National University of Rio Cuarto (Argentina) during their freshman year. It also addresses their past academic performance and how it impacts their current academic performance. The study group consisted of 86 students from a 2018 cohort, 53% of whom were high academic performers and the remaining 47%, low academic performers. The study subjects were asked to complete the survey, Questionnaire on Freshman Year Academic Performance to obtain the required data for the study regarding student academic standing during their first year. The questionnaire included a section that specifically addressed learning strategies employed by students. Findings from this quantitative and qualitative study reveal a positive relationship between the use of certain complex cognitive, metacognitive and resource management strategies and good academic performance. Furthermore, more than 50% of students stated that they changed their study habits after entering university, particularly, with regards to the time they devoted to studying. According to high-achieving students time concurs with better planning, organizing and managing their time, as well as finding the most effective strategies to meet their learning goals (55%). Low academic performers stated that they altered their habits by incrementing the hours spent studying (82%), which does not always ensure good grades, unless the student examines their own performance and adopts a more profound approach to the course materials.